Web information gathering processes for gold and silver price information - Katuk, Norliza; Zakaria, Nur Haryani; Mohd Shariff, Afiq Aisamuddin; Al-Ghushami, Abdullah Hussein; Yusoff, Muhammad Hilmi (2013)
This paper presents a research on product-specific web information gathering concept that intends to improve web searching through conventional search engines.Search engines are useful for searching general information; however, the results are not always accurate because they return the results based on key-words occurrences, but not accurateness.Further, users must filter and organize the information accordingly to make the information meaningful.Users must also visit multiple websites independently to check whether the information is relevant.These processes are tedious and very time consuming especially for users who search for specific products information Hence, we propose a web information gathering model that aims to provide a standard for developing product-specific web searching tools. It was applied in a mobile application called Gold-Trader. The mobile application provides gold and silver prices information to individual or personal traders.It can help individual or personal traders to monitor and compare gold and silver prices from multiple websites without the needs to visit them individually.